ASSESSMENT OF METABOLIC SYNDROME AND ITS RISK FACTORS IN WOMEN BY AGE, SOCIOECONOMIC STATUS, AND LIFESTYLE FACTORS (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Metabolic syndrome (MetS) is a complex condition that elevates the risk of cardiovascular disease, type 2 diabetes, and other chronic disorders in women. This study examines the prevalence of MetS and its associated risk factors, with particular attention to age, socioeconomic status, and lifestyle behaviors. Evidence shows that the prevalence of MetS rises with age, especially during perimenopause and postmenopause. Key lifestyle determinants, including unhealthy diet, physical inactivity, and obesity, are strongly linked to MetS development. Socioeconomic factors, such as education, income level, and access to healthcare, further modify the risk. Reproductive health aspects, including polycystic ovary syndrome and pregnancy-related complications, also contribute to metabolic abnormalities. Understanding the interactions between these factors can guide effective prevention and intervention strategies. Overall, integrated approaches that combine lifestyle modification, health education, and regular screening are essential to mitigate the burden of MetS among women across different age groups and social settings.
Keywords: Metabolic syndrome, women, risk factors, lifestyle, socioeconomic status, age, obesity, reproductive health.